PERILAKU MENYIMPANG ANAK SD MENCURI UANG TEMAN - Maula Saputri; Rosa Sanora, Dia Cikal Santri Ananda, Randa, Yuni, Nur Alfilaila, Sriliza (JURNAL PENDIDIKAN DAN KEGURUAN, 2026)
This journal aims to describe and analyze the deviant behavior carried out by students in grade V as well as the efforts made by teachers in overcoming deviant behavior of students at State Elementary School 15 Perigi Parit, Teluk Keramat District. This study uses a qualitative research approach with a descriptive research type. The data collection technique in this study uses interview and observation techniques. The data analysis techniques used are data collection, data reduction, and conclusion drawn. The results of this study show that: 1. Deviant behavior committed by students in grade V at State Elementary School 15 Perigi Parit, Teluk Keramat District in the form of taking or stealing friends' money. 2. The efforts made by teachers in overcoming deviant behavior of students at State Elementary School 15 Perigi Parit are first, preventive actions through Monday ceremony activities, Quranic reading activities, congregational prayers, and the provision of discipline to students. The second curative action is by providing advice, direction, guidance, approaches to students, and giving special attention to students with problems. The repressive effort here is by giving sanctions to students in the form of cleaning, additional assignments, as well as warning letters, and letters of appeal to parents